Pilgrimage and Peregrination: Contextualizing the Saikoku Junrei and the Shikoku Henro - Hoshino, Eiki (Japanese journal of religious studies, 1997)
This article provides a general theoretical overview ofJapanese pilgrimage while concentrating on the Saikoku and Shikoku multi-site pilgrimages. Japanese pilgrimage practice is placed in a broader perspective by comparison with practices in other countries. Pilgrimages in the Buddhist cultural sphere of Asia are generally of the multi-sited circuit-type, while those in Europe and the Middle East are single-line pilgrimages headed towards one major site. Victor Turner's observations regarding the differing attitudes of pilgrims when embarking on their journey and those on the way home would seem to be less appropriate in the case of these circuit-type pilgrimages.